Möjligheter att minska kväveutlakningen genom att anpassa kvävegödslingen till variationer inom stråsädesfält - Nilsson, Cecilia (2010)
Due to excess precipitation that cause runoff, all soils in Sweden naturally leaches nitrogen. High leaching from arable land is an environmental problem when the runoff reaches waters. In the international agreement, Baltic Sea Action Plan, the aim is to reduce the runoff of nutrients. Sweden has agreed to reduce its load of e.g. nitrogen to the Baltic Sea. One of the proposed measures is an increased use of site-specific N-fertilization, which has been shown to increase nitrogen use efficiency and therefore also reduce the nitrogen runoff. Either yields are increased with the same total amount of nitrogen, or the total quantity of nitrogen is reduced with preserved yield levels, which is profitable for the farmers.